Secretion of α-immunoreactive inhibin by human pre-embryos cultured in vitro - Phocas, I.; Sarandakou, A.; Rizos, D.; Dimitriadou, F.; Mantzavinos, T.; Zourlas, P.A. (Human Reproduction, 1992)
α-Immunoreactive inhibin was measured using an enzyme immunoassay kit in the culture medium (Ham's F-10 medium supplemented with 14% heat-inactivated human serum) from day 3 or 4 to day 14 post-fertilization of 31 surplus pre-embryos from eight women participating in an in-vitro fertilization programme. Inhibin secretion was demonstrated in all of them from the fourth day after fertilization (mean ± SEM: 3.0 ± 0.7U) and was independent of the morphological development of pre-embryos (2-4 cells, n = 4; 6-8 cells, n = 4; 8-10 cells, n = 9; 10-12 cells, n = 4; morulae, n = 5 and blastocysts, n = 4). On days 7,10,13 and 14 post-fertilization, mean inhibin values ± SEM for non-disintegrated pre-embryos were respectively: 6.5 ± 0.9U, 12.3 ± 2.0U, 16.8 ± 3.2U and 20.2 ± 3.7U; however, when disintegration was noted on days 10 and 13 after fertilization, inhibin mean values were 9.0 ± 1.4U and 8.4 ± 1.7U respectively. Inhibin levels were significantly correlated with human chorionic gonadotrophin levels in the same culture media only on day 13, while correlation with pregnancy specific β1-glycoprotein occurred on day 7 post-fertilization. In conclusion, early human pre-embryos secrete α-immunoreactive inhibin before the cytotrophoblast is formed. This secretion increases significantly with time when development is continued, while disintegration is followed by a net decline in the rate of inhibin release.